Correlations Between Lexical Error And Writing Competence In Narrativetext - Hellen Wijaya (UKMC International Conference (UKMC IC) Proceedings, 2024)
This research explores the correlations between writing competence and lexical error in narrative texts among twelve college students from Musi Charitas Catholic University, majoring in English Language Education Study Program. Since writing is a crucial skill in learning foreign languages, as it helps students to increase their understanding of lexical items and cover the ideas in narrative text. Proper use of vocabulary is essential for clear communication, and lexical error can lead to misunderstandings or misinterpretations. Researcher uses quantitative design for this study with collecting data that are collected from the narrative texts of the students’ writings that are rated by two raters from two different universities. The result of this research shows that there is a strong correlation between writing competence and lexical error. The factors that give influence to this are vocabulary knowledge, prior writing experiences, and the teaching environment. Lastly, it should be implied in teaching situations where students are given more chances to increase their knowledge of learning vocabulary by increasing writing activity in a good learning environment so that students feel more motivated in writing activity.